Effect of Actinomycin D on Virus-induced Ribonucleic Acid Polymerase Formation in Foot-and-Mouth Disease Virus-Infected Baby Hamster Kidney Cells - Polatnick, Jerome (1967)
Actinomycin D, at a concentration that inhibits cellular ribonucleic acid (RNA) synthesis, inhibited the production of foot-and-mouth disease virus-induced RNA polymerase in baby hamster kidney cells. Inhibition was proportional to exposure time and reached 85% when actinomycin D was added 90 min before infection. Polymerase production was inhibited to the same extent in growth and minimal media, and the kinetics of its appearance were slightly different than in untreated cells. Enzyme preparations from actinomycin-treated cells having one-third to one-tenth the activity of untreated samples gave products with RNA profiles similar to those of controls. The 37S viral peak, 20S ribonuclease-resistant peak, and 26 to 28S peaks were present in all cases. Actinomycin D did not consistently inhibit virus production in either medium. Insulin did not prevent the actinomycin induced inhibition of polymerase and virus production from occurring.